ظاهرة الانزياح اللغوي في القران الكريم سورة مريم انموذجا - حمريط, هيثم (My University, 2017)
Abstract : This study -which contains three chapters- examines the phenomenon of language displacement in Quran through surat Maryam, According to a method stylistic wich concentrates on general linguistic data, and invests language levels critical and aesthetic investment. This study is characterized by trying to treat the phenomenon of displacement from its theoretical part ،besides an applied study on all the Sura, by clarifying the Quranic method in terms of vocal, morphological, syntactic and semantic. Which clearly shows that the words of glorious Allah contain all aesthetics of linguistic displacement, and the stylism of displacement is perfectly mature.
Keywords: الانزياح -مستويات اللغة- الاسلوب - اللسانيات - التركيب.